Relationship of capital adequacy requirement with profitability, risk and capital management. - Oh, Zhenhe. (2008)
Countless previous researches have touched on the relationship of capital adequacy ratio with the various aspects of banks’ financial performance and behavior, more specifically the profitability, the insolvency risk as well as the management of capital internally. This paper attempts to extend the research by analyzing recent data from banks in the U.S. and covering the time frame between 2001 and 2005. Our study also takes into account the size and scope of banks’ operation. With a focus set out to understand more about the effect of capital requirements on the different aspects of banks, we expect that the results from this study will assist banks in their preparation for the impending implementation of the Basel II Accord. Our empirical evidence suggests that capital requirement has no strong relationship with the profitability, insolvency risk and capital management of a bank. Similarly, the type of a bank also bears little significance operational wise. However, the size of a bank has a significant impact on banks’ profitability and capital management, albeit positively for the former and negatively for the latter. It has little effect on the insolvency risk which a bank is exposed to.